Microbial Biofilms as a Risk Factor for Acantahmoeba keratitis - Norouzi, Maryam; Niyyati, Maryam; Behniafar, Hamerd (Novelty in Biomedicine, 2022)
Members of the protozoan genus Acanthamoeba are free-living amoebas and the primary causative agent of amoebic keratitis and granulomatous encephalitis. Amoebic keratitis mainly occurs in individuals who wear soft contact lenses following trauma and exposure to contaminated sources. As the survival, growth, and multiplication of this protozoan increases in biofilms, which is the microbial accumulation, several cases of amoebic keratitis have been reported as co-infections with bacteria, especially Pseudomonas aureginosa. Pseudomonas improves the binding of this protozoan to soft lens surfaces by its special surface enzymes, resulting in Acanthamoeba keratitis and sometimes mixed infection. Biofilm accumulates microorganisms, including bacteria and fungi, on living and non-living surfaces. The firm attachment of these microbial accumulations to the surface can cause various diseases and resistance to treatment. The critical point is that bacteria have less destructive effects in the plantonik state, and when the specific signals of these microbiome cause the recall of other microorganisms and their interaction, they lead to problems. Unfortunately, the ocular defense barrier, which includes the eyelids, lacrimal glands, and tears, cannot kill microbial agents when microorganisms accumulate and adhere firmly to the lens surfaces. Due to the great importance of AK, especially in medical contact lens users, biofilm formation is an important issue that has been considered in recent years. Biofilm formation-induced drug resistance, which is caused by the disproportionate density of microorganisms on the inner and outer surfaces of the biofilm. There are several ways to prevent the formation of biofilms on the surfaces of contact lenses, including the use of antimicrobial peptides and various antibiotics and coating them on the inner surface of contact lenses to slow-release of antibiotics and prevent biofilm formation. In the present review article, we aimed to introduce biofilms as one of the important risk factors for developing Acanthamoeba keratitis and prevention ways of biofilms formation.